Development of the conductivity type inversion caused by thermal double donors' formation in p-type high-resistivity silicon. (1st March 2023) - Li, Minghao; Liu, Yun; Wei, Tao; Dai, Rongwang; Wang, Hao; Xue, Zhongying; Wei, Xing
Abstract: The formation of thermal double donors (TDDs) during the iso-thermal annealing at 450 °C in low-oxygen and high-resistivity silicon was quantitatively investigated, and the oxygen related power parameter x for low-oxygen and high-resistivity silicon was obtained. Excessive TDDs formed in the p-type high-resistivity silicon during the device manufacturing process will invert the conductivity to n-type. A quantitative relationship between the critical wafer start resistivity and oxygen concentration in p-type high-resistivity silicon was obtained. The p-type conductivity can be maintained after the device fabrication by controlling the resistivity below the critical resistivity corresponding to the oxygen concentration in p-type high-resistivity silicon.